The benefits and risks of experimental co-production: the case of urban redesign in Vienna - Bartenberger, Martin; Szescilo, Dawid (2016)
Building on the literature on co-production and the (pragmatist) literature on experimentalist policy-making we introduce and evaluate a novel form of co-production: experimental co-production. We propose a model of this specific form including a list of not only potential benefits but also possible risks and costs. We illustrate and examine this model of experimental co-production by drawing on the case study of a major urban planning initiative in Vienna, Austria that included an experimental co-testing phase. We find that while the expected benefits of experimental co-production were partly realized for the citizens involved, the city government faced major political costs.
Keywords: Urban design - Vienna; Urban design